The making of public investments: Champions, coordination, and characteristics of nutrition interventions - Mogues, Tewodaj; Billings, Lucy (International Food Policy Research Institute, 2015)
To better support allocations of public investment—especially where needs are high and resources scarce—it is first instructive to have an in-depth understanding of what drives realized public investment behavior. The study applies a process-tracing approach to test and build theories around models that center on the characteristics of investments and the role of agents. In the context of public investment in nutrition in a low-resource economy, the analysis finds that public decisionmakers strongly favor highly visible nutrition investments with a short lag between spending incurred and outcomes achieved. Coordination among agents that allocate funds to nutrition takes mostly a spatial nature, resulting in greater geographic equity of public investment. Champions as change agents have an influential role in attracting more funding to nutrition and improving its allocation, but their influence is fleeting and difficult to sustain.